Implementasi Pembelajaran Jarak Jauh Berbasis Platform Kelase sebagai Sumber Belajar Siswa di SDIT Lentera Ilmu - Amalia, Amalia; Dorahman, Boy; Mawardi, Mawardi (Lembaga Yasin AlSys, 2023)
The Covid Pandemic outbreak has become an international disaster that has occurred almost all over the world which has had an impact on many lives, including the field of education which currently uses distance learning. This study aims to determine the implementation of classroom-based distance learning as a learning resource for students, besides that this research also aims to find out how to use the classroom platform for distance learning and how to evaluate and follow up on the implementation of classroom-based distance learning as a resource. studied in class IV at SDIT Lantera Sciences, Tangerang City. Data collection techniques in this study are by using observation, interviews, and documentation. This study used 29 people as informants. The application of the class platform at SDIT Lentera Ilmu as a learning resource can provide many conveniences in the distance learning process that is currently ongoing. Teachers and students already understand the use of the classroom platform as a learning resource, and have received support from foundations, schools, and students' parents in its implementation. The class platform will still be used during face-to-face learning.